2017
DOI: 10.1016/j.ejmech.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Explicit treatment of active-site waters enhances quantum mechanical/implicit solvent scoring: Inhibition of CDK2 by new pyrazolo[1,5-a]pyrimidines

Abstract: We present comprehensive testing of solvent representation in quantum mechanics (QM)-based scoring of protein-ligand affinities. To this aim, we prepared 21 new inhibitors of cyclin-dependent kinase 2 (CDK2) with the pyrazolo[1,5-a]pyrimidine core, whose activities spanned three orders of magnitude. The crystal structure of a potent inhibitor bound to the active CDK2/cyclin A complex revealed that the biphenyl substituent at position 5 of the pyrazolo[1,5-a]pyrimidine scaffold was located in a previously unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 60 publications
0
22
0
1
Order By: Relevance
“…These results may be due in part to the relatively well‐conserved geometry of the CAII binding site. Obtaining correlation without considering explicit waters does not contradict previous findings that waters are important in P–L binding . Rather, it demonstrates that the implicit COSMO model can capture some of these effects in some P–L systems.…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…These results may be due in part to the relatively well‐conserved geometry of the CAII binding site. Obtaining correlation without considering explicit waters does not contradict previous findings that waters are important in P–L binding . Rather, it demonstrates that the implicit COSMO model can capture some of these effects in some P–L systems.…”
Section: Resultsmentioning
confidence: 47%
“…Obtaining correlation withoutc onsidering explicit waters does not contradict previous findings that waters are important in P-L binding. [9,15,34] Rather,i td emonstrates that the im-plicit COSMO model can captures ome of these effects in some P-Ls ystems. The correlation of the classical SFs remained low.I nterestingly,t he "single protein conformation" approximation improved the DOCK 6r esults.…”
Section: Scoringmentioning
confidence: 98%
See 2 more Smart Citations
“…[12,[18][19][20] Many studies on various biomolecular complexes have shown that the use of the SQM methods through each of the methodologies has led to more accurate estimation of complex geometry and binding energy and consequently has increased the docking accuracy. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In this study, a post-docking optimization with the different popular corrected SQM Hamiltonians has been performed for the docking results of a series of human cyclin-dependent kinase 2 (CDK2). The CDK2 is a serine/ threonine-protein kinase that is activated by binding to a regulatory cyclin protein for the cell cycle progression and transcription.…”
Section: Introductionmentioning
confidence: 99%